2021
DOI: 10.1159/000514319
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Responders and Exploring Mechanisms of Action of the Endobronchial Coil Treatment for Emphysema

Abstract: Background: So far, 3 randomized controlled trials have shown that the endobronchial treatment using coils is safe and effective. However, the more exact underlying mechanism of the treatment and best predictors of response are unknown. Objectives: The aim of the study was to gain more knowledge about the underlying physiological mechanism of the lung volume reduction coil treatment and to identify potential predictors of response to this treatment. Methods: This was a prospective nonrandomized single-center s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Nine trials were found eligible for inclusion, and all accepted to share IPD (shown in Fig. 1 ) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. One trial was unable to supply sufficient data to identify the original study population in the supplied IPD and was therefore excluded from the meta-analysis [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine trials were found eligible for inclusion, and all accepted to share IPD (shown in Fig. 1 ) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. One trial was unable to supply sufficient data to identify the original study population in the supplied IPD and was therefore excluded from the meta-analysis [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Details on the record selection can be found in the supplement. Five trials reported outcomes at 3-month follow-up [ 14 , 16 , 18 , 21 , 22 ], four trials at 6-month follow-up [ 13 , 15 , 17 , 19 ], and three trials at 12-month follow-up after final treatment [ 15 , 17 , 18 ] (shown in Fig. 1 , and in online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…The working mechanism is explained as follows: compression of the lung parenchyma reduces the lobar RV and increases airflow to untreated regions; thereby, hyperinflation may be reduced and diaphragm function may improve. By pulling together the most destroyed segments, the elastic recoil of the lung improves, ameliorating expiratory flow and air trapping [ 110 , 111 ]. This is also reflected by the beneficial effect of coil-associated opacities [ 73 , 112 ].…”
Section: Bronchoscopic Lung Volume Reductionmentioning
confidence: 99%
“…Gala-Therapeutics' RheOx technology involves the delivery of a pulsed electronic field (high frequency, short-duration, nonthermal electrical fields). 21 This targeted energy delivery is intended to cause goblet cell death by disrupting cellular homeostasis, leading to processes such as osmotic swelling and apoptosis. 22 This cell death does not destroy the architectural function of the tissue, permitting subsequent regeneration of normalized epithelium and a reduction in airway mucus production.…”
Section: Chronic Bronchitismentioning
confidence: 99%